Implementation of Team Games Tournament Learning Model to Improve English Vocabulary - Shafa Ghina Adhaniyah (Universitas Islam Al-Ihya Kuningan, 2024)
The aim of this research is to improve the English vocabulary of the fourth grade by using an interesting learning model for students, namely Team Games Tournament. This research method used the classroom action research method or CAR with a qualitative and quantitative approach. The subjects in this research was class IV SDN Kutaraja with a total of 22 students consisting of 12 male and 10 female students collaboratively between researchers and teachers with data collection techniques using test sheet instruments, observation sheets and documentation. The results of the research showed that the average score pretest is 64,32 and in KKM the students is 63,63%. In cycle I, the average score of posttest is 76,8 and the results of KKM is 77,27%. In cycle II, the average score of posttest is 88,40 and the results of KKM is 90,90%. The results of students observation, in cycle I is 76,7% and in cycle II is 88,88%. For the results of teacher observation, in cycle I is 76% and in cycle II is 86%. It means that there is an improvement from pretest, posttest, teacher and students observation. So, it can be said Team Games Tournament can improve the students English Vocabulary.